CHEMICAL ANALYSIS OF FISH FLESH AND FLOUR FROM GIANT SNAKEHEAD FISH (Channamicropeltes) - Shabrina Nur Fakhriah; Rahman Karnila; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was aimed todetermine the chemical compositionof fish flesh and flour from giant snakehead fish (Channamicropeltes). The research method consisted of 2 stages 1) Preparation and chemical analysis of fish flesh and 2) Making and analyzing chemichal of  flour from a giant snakehead fish . The observed parameters in stage 1 were the proportion of fish body parts and chemical analysisof fish flesh. The observed parameters in stage 2 were  the yield of flour and chemical analysis moisture, ash, protein, fat,and carbohydrate (by different). The results showed that the proportion of fish flesh fromgiant snakehead fish was the largest proportion in the headby 34,23%among other body parts.Moreover, the chemical composition of fish flesh from giant snakehead fish was moisture 80,25%(wb) moisture,4,68%(db)ash, 82.98% (db) protein and 4,59% (db) fat and  the carbohydrates 7,75% (db). Furthermore, the yield of flour from giant snakehead fish was 92,49% and its chemicalwas 9,06% (wb) moisture, 7,51% (db) ash, 79,26% (db) protein and 3,07 % (db) fat and the carbohydrate of 10,16% (db).Keywords: Chemical Composition,Giant snakehead, Yield